1989
DOI: 10.1002/anr.1780320304
|View full text |Cite
|
Sign up to set email alerts
|

Class ii major histocompatibility complex gene sequences in rheumatoid arthritis. The third diversity regions of both DRβ1 genes in two DR1, DRw10–positive individuals specify the same inferred amino acid sequence as the DRβ1 and DRβ2 Genes of a DR4 (Dw14) haplotype

Abstract: The DRl and DRwlOP, chain genes were isolated from each of 2 individuals with rheumatoid arthritis who were heterozygous for these class I1 major histocompatibility complex specificities. The sequences of the DRIP, chains from both patients were identical, differing from previously reported DRP, chains of individuals without RA by 2 amino acid substitutions, at positions 85 (Val-Ala) and 86 (Gly-Val), and by a silent mutation at the last nucleotide of codon 78 (C-T), resulting in the loss of a Pst I restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The association of HLA-DR4 with seropositive RA (1 0) seems to be due to the Dw4 and Dw14 subtypes, which share equivalent sequences in their third HVR, whereas the DR4 subtypes, Dw13 and DwlO, which differ by nonconservative substitutions in this region (33), do not associate with the disease (1 1). Since our patients with seropositive RA had only a weaker association with the DR4 haplotype, we could predict, according to the shared epitope hypothesis (5,34), that these patients would either have a different crucial third HVR involved in RA susceptibility or the third HVR of the above-mentioned DR4 subtypes would be unusually represented in other DR alleles. The relationship of the Bum HI 3.6-kb and 4.5-kb fragments with such genetic susceptibility elements remains to be elucidated through a detailed sequence analysis of these fragments.…”
Section: Discussionmentioning
confidence: 88%
“…The association of HLA-DR4 with seropositive RA (1 0) seems to be due to the Dw4 and Dw14 subtypes, which share equivalent sequences in their third HVR, whereas the DR4 subtypes, Dw13 and DwlO, which differ by nonconservative substitutions in this region (33), do not associate with the disease (1 1). Since our patients with seropositive RA had only a weaker association with the DR4 haplotype, we could predict, according to the shared epitope hypothesis (5,34), that these patients would either have a different crucial third HVR involved in RA susceptibility or the third HVR of the above-mentioned DR4 subtypes would be unusually represented in other DR alleles. The relationship of the Bum HI 3.6-kb and 4.5-kb fragments with such genetic susceptibility elements remains to be elucidated through a detailed sequence analysis of these fragments.…”
Section: Discussionmentioning
confidence: 88%
“…It has been shown that DRl and the DR4 subtypes that predispose to RA share an epitope near amino acid residues 70 and 71 of the DRpl chain, and this common epitope has been implicated in the predisposition for RA (48)(49)(50)(51). A similar phenomenon might be true for our RA patients with ACA.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes-prone NOD mice and their MHC class II (I-A NOD ) have been viewed as an example for this situation (25). Given the high frequency of most autoimmune diseaseassociated HLA-DR and -DQ alleles in the population and the normal cellular immune function in the vast majority, we consider this mechanism unlikely in MS. (c) Either polymorphic residues of the T cell receptor (TCR)-exposed surfaces of the α-helical regions of DR/DQ-α and -β chains, such as the "shared motif" in rheumatoid arthritis-associated class II molecules (26) or TCR-contacting amino acids of the antigenic peptide, or both, could select an autoimmune-prone T cell repertoire. Gross abnormalities in T cell repertoires do not exist in MS patients according to current data (see below).…”
mentioning
confidence: 99%